Professional Madrasah Teachers in Teaching: The Influence of Gender and the Length of Certification of Madrasah Teachers - Tambak, Syahraini; Mahfud, Choirul; Latipah, Eva; Sukenti, Desi (IAIN Samarinda, 2021)
Developing professional madrasah teachers are increasingly popular in the teaching classrooms. But regarding developing professional madrasah teacher accuracy in teaching, mixed results are reported without clear reasons for this. This article addresses the impact of gender and length of certification on developing professional madrasah teacher accuracy in teaching classrooms. To develop the accuracy of the developing professional madrasah teacher, madrasah teacher length of certification and gender are used as a reference. A research project, which deals with the developing professional teacher in madrasah teachers using questionnaires, was carried out in two types of Madrasah Aliyah (public and private madrasah) at seventy-five madrasahs. Data from 325 madrasah teachers were collected and involved in this research. This analysis is differentiated based on the level, gender, and level of the length of certification of madrasah teachers in the developing professional teacher competencies being assessed. The results show that the accuracy of the developing professional teacher is low and is related to the gender of the madrasah teacher, that men perceive themselves to be higher in the developing professional teacher than women, and that even length of certification analysis with developing professional competence and implementation in the classroom. Madrasah teacher length certification more than 10 years are higher than teachers who certified between 5-10 years and more accurate than teachers who certified less than 5 years with the ability to developing professional madrasah teacher that is low. It is necessary to examine the reasons behind this difference and to look for steps to improve the accuracy of the developing professional madrasah teacher.